Financial Management in the Slovak Health Insurance Sector during the COVID-19 Pandemic - Natália BARTEKOVÁ; Jana KAJANOVÁ (Communications of International Proceedings, 2022)
The health insurance sector is one of the areas that has been impacted quite heavily by the Covid-19 pandemic. Our research aimed to compare the development of selected financial indicators of selected companies operating in the health insurance sector in Slovakia and to determine the effectiveness of financial management from the aspect of the pandemic. We examined the following indicators for the three largest players in the Slovak market: Return on Assets, Return on Equity, and Net Profit Margin. By applying the IN05 model bankruptcy possibilities were predicted for health insurance companies. According to this study, the Union Health Insurance Co. Ltd. used its assets and also equity as the most effective in the health insurance sector during the period of the pandemic. The highest net profit margin generated in 2020 was produced by Union Health Insurance Co. Ltd. even though the value was negative. Therefore, Union Health Insurance Co. Ltd. takes the best position in terms of financial management effectiveness in the health insurance sector.
Keywords: health insurance sector; financial management; profitability indicators